Evaluation of streamflow prediction with considered the climate change impact at Sungai Kechau, Pahang - Muhammad Aminur Rasyid, Othman (2018)
Streamflow nowadays becomes fluctuated due to climate change impact that causes various disasters that threaten the environment and it has been measured that a greater negative impacts on human society. General Circulation Models (GCM) stated that the increment of concentration of greenhouse gases will have significant implications for climate at regional scales. In this simulation which is “downscaling” techniques are used to describe as a decision support tool for local climate change impacts. Statistical Downscaling Model (SDSM) is beneficial the rapid development of multiple, low cost, single-site scenarios of daily weather variables and future regional climate force. The application of SDSM is applied to simulate with respect to the generation of daily temperature and rainfall scenarios for Kechau River, Pahang for 2020-2099. However, in this studies is supported on the capability of IHACRES model in area where hydrological data has a limitation factor. The IHACRES model is being applied in a regionalization approach to develop streamflow prediction. Using IHACRES rainfall-runoff model, it is a non-linear loss module which is to calculate the effective rainfall and routing a linear module converting effective rainfall into streamflow.